Nascent RNA antagonizes the interaction of a set of regulatory proteins with chromatin - Skalska, L; Begley, V; Beltran, M; Lukauskas, S; Khandelwal, G; Faull, P; Bhamra, A; Tavares, M; Wellman, R; Tvardovskiy, A; Foster, BM; Ruiz de Los Mozos, I; et al. (Cell Press, 2021)
A number of regulatory factors are recruited to chromatin by specialized RNAs. Whether RNA has a more general role in regulating the interaction of proteins with chromatin has not been determined. We used proteomics methods to measure the global impact of nascent RNA on chromatin in embryonic stem cells. Surprisingly, we found that nascent RNA primarily antagonized the interaction of chromatin modifiers and transcriptional regulators with chromatin. Transcriptional inhibition and RNA degradation induced recruitment of a set of transcriptional regulators, chromatin modifiers, nucleosome remodelers, and regulators of higher-order structure. RNA directly bound to factors, including BAF, NuRD, EHMT1, and INO80 and inhibited their interaction with nucleosomes. The transcriptional elongation factor P-TEFb directly bound pre-mRNA, and its recruitment to chromatin upon Pol II inhibition was regulated by the 7SK ribonucleoprotein complex. We postulate that by antagonizing the interaction of regulatory proteins with chromatin, nascent RNA links transcriptional output with chromatin composition.